PERUBAHAN SOSIAL, BUDAYA DAN EKONOMI DI KAMPUNG KAUMAN SEMARANG 1962-1998 - Azizah, Nur (Journal of Indonesian History, 2014)
Kauman Semarang is Islamic Student’s village. Whose Majority are native’s Java people that have religion of Islam, there’s also Arabic and Chinese descendant. The purpose of this study was to (1) determine how the general picture of the village Kauman Semarang; (2) determine the development of social, cultural and community Kauman in 1962-1998; (3) determine the development of Community Economic Kauman years 1962-1998. The method used in the form of historical method, which consists of four stages, namely heuristic, criticism, interpretation, and historiography. The results showed that Kauman located in downtown Semarang, apparently influenced the development of community life like in terms of social, cultural, and economic. In the period 1962-1998, the development of community life so visible. In terms of social and cultural, villagers Kauman diverse not only native Java, but are also a few ethnic, make them live side by side in harmony is maintained, the culture was still preserved as Dugderan which is the result of acculturation. In economic terms, with the market Johar and market Yaik, Kauman region changed over time also become regional trade and services, traditional houses Kauman replaced with a row of shop (shop houses) along the way Kauman Kingdom.